IMPACT OF WASHING SOLUTIONS ON CHEMICAL COMPOSITION AND PHYSICO-CHEMICAL PROPERTIES OF SURIMI-LIKE MECHANICALLY DEBONED TURKEY MEAT - Oleg GALENKO (Stefan cel Mare University of Suceava, 2020)
The impact of washing solutions on mechanically deboned turkey meat (MDM) was evaluated with the aim to produce surimi-like material using solutions of succinic (pH 5.9) and lactic acid (pH 5.8). Inorganic phosphoric acid was found to be the strongest ionization constants, with tartaric, then citric, malic, lactic and succinic acids. In washed samples found that moisture content at the end of the study was 87.6%–92.7%, fat 1.04%–3.2%, protein 17.4–18.2%, ash 0.079–0.086%. The number of washing significantly influenced the increase in moisture content and the reduction of fat content. The moisture content increased from 65.0% (P <0.05) for unwashed masses to 69.3–74.1% after the second washing and to 76.2–79.7% after the third washing. Obtained surimi-like material may have a moisture content in the range of 73 to 80%, but 78% moisture content is technologically the best. During the experimental studies of turkey MDM it was found that the best indicators were achieved for minced meat washed with 0.3% succinic acid at ambient temperature of 15°C, 1:4 ratio of turkey MDM to acid solution, 20 min mixing time and 20 min centrifugation. Surimi-like material washed with succinic acid had higher pH and moisture retention capacity, and showed better colour changes than unwashed turkey MDM and other surimi-like materials. This study demonstrates that succinic acid solution provides the achievement of desired surimi-like material with the best technological quality and low fat content.